2019
DOI: 10.1001/jamanetworkopen.2019.16097
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Physician Depressive Symptoms and Medical Errors

Abstract: This systematic review and meta-analysis examines whether physician depressive symptoms are associated with the risk for perceived or observed medical errors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
75
2
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 112 publications
(84 citation statements)
references
References 68 publications
3
75
2
4
Order By: Relevance
“…In the present study, the prevalence of depressive, anxiety, and comorbid depressive and anxiety symptoms among Chinese frontline medical staff responding to the COVID-19 outbreak was 40.93%, 31.78%, and 26.00%, respectively, which was higher than reported peacetime estimates as well as estimates from the initial phase of the SARS epidemic [19][20][21][22][23]. A previous study conducted in southern China has reported that 28.13% of physicians had depressive symptoms, 25.67% had anxiety symptoms, and 19.01% had comorbid depressive and anxiety symptoms [20].…”
Section: Discussioncontrasting
confidence: 75%
“…In the present study, the prevalence of depressive, anxiety, and comorbid depressive and anxiety symptoms among Chinese frontline medical staff responding to the COVID-19 outbreak was 40.93%, 31.78%, and 26.00%, respectively, which was higher than reported peacetime estimates as well as estimates from the initial phase of the SARS epidemic [19][20][21][22][23]. A previous study conducted in southern China has reported that 28.13% of physicians had depressive symptoms, 25.67% had anxiety symptoms, and 19.01% had comorbid depressive and anxiety symptoms [20].…”
Section: Discussioncontrasting
confidence: 75%
“…A systemic review and meta-analysis reported that according to a pooled analysis of 54 observational studies, the prevalence of depression or depressive symptoms was approximately 28.8%, ranging from 20.9% to 43.2% in individual studies depending on the scale used [ 12 ]. As our study reports high levels of depressive and anxiety symptoms, urgent psychological intervention plans are needed to prevent burnout and suicide risk in physicians and decrease the risk of medical errors [ [37] , [38] , [39] ].…”
Section: Discussionmentioning
confidence: 99%
“…Causes of burnout include: increased clinical demands, inadequate staffing patterns, decreased control, poorly functioning teams, role ambiguity, moral distress, reimbursement issues, decreased time with patients, difficulty balancing personal and professional lives, inefficiency of the electronic medical record and isolation. Burnout also contributes to increased medical errors, patient dissatisfaction, high turnover rates and substantial financial losses (Hall, Johnson, Watt, Tsipa, & O’Connor, ; Pereira‐Lima et al, ; Willard‐Grace et al, ). For every newly licensed registered nurse who leaves their job in the first year of practice, it costs the institution up to three times the nurse’s annual salary when factoring in the costs associated with recruitment, training and orientation (Unruh & Zhang, ).…”
mentioning
confidence: 99%